Local wisdom of the Lingga Malay Community in harvesting and transporting sago in Lingga District, Riau Islands, Indonesia - PRIMADHIKA AL MANAR; ERVIZAL A.M. ZUHUD; NURI ANDARWULAN; ANAS MIFTAH FAUZI; MOCHAMAD HASJIM BINTORO; AGUS HIKMAT; SYAWALNI HERMANIDA (Society for Indonesian Biodiversity, 2026)
Abstract. Al Manar P, Zuhud EAM, Andarwulan N, Fauzi AM, Bintoro MH, Hikmat A, Hermanida S. 2026. Local wisdom of the Lingga Malay Community in harvesting and transporting sago in Lingga District, Riau Islands, Indonesia. Biodiversitas 27 (4): d270415. https://doi.org/10.13057/biodiv/d270415. Sago (Metroxylon sagu) plays an important role in the food system, culture, and ecological resilience of coastal communities in Indonesia, including the Lingga Malay Community in the Riau Islands, Indonesia. However, systematic documentation of traditional ecological knowledge (TEK) related to sago harvesting and transportation in this region remains limited. This study aimed to analyze local wisdom practices associated with sago harvesting and transportation among the Lingga Malay Community. A qualitative approach was applied through in-depth interviews with 100 informants across ten villages, participatory observation, and a literature review. Data were analyzed using thematic analysis supported by coding and triangulation techniques. The results reveal that the community possesses a well-developed TEK system for identifying harvestable sago palms based on morphological indicators and ecological conditions. Harvesting practices combine traditional techniques with selective semi-mechanized tools adapted to local environmental constraints. In addition, transportation systems are primarily water-based, using rakit and small motorized boats (pompong), reflecting adaptive strategies to the archipelagic and riverine landscape of Lingga. The utilization of sago residues further demonstrates resource-efficient practices embedded in local socio-ecological systems. These findings highlight the role of traditional knowledge in supporting adaptive resource management and sustaining local livelihoods in island ecosystems.